O mistério da Encarnação na reflexão teológica de Luís F. Ladaria - Marcolino, Reginaldo (2011)
Through the reflection of the theologian Luis F. Ladaria, understand the man in the grace of Christ, being from this, undestand the dimension of human being in their relationship with God, because, this man was created in the image of God to reach the realization of the perfect likness, knowing that, will be the light of the mistery of the incarnation that can be understood as the human deification. The author follows the path of understanding the human sonship